2020
DOI: 10.1016/j.heliyon.2020.e03187
|View full text |Cite
|
Sign up to set email alerts
|

MiR-502 is the first reported miRNA simultaneously targeting two components of the classical non-homologous end joining (C-NHEJ) in pancreatic cell lines

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers. Acquired inherited and/or somatic mutations drive its development. In order to prevent the formation of these mutations, precise and immediate repair of any DNA damage is indispensable. Non-homologous end-joining (NHEJ) is the key mechanism of DNA double-strand break repair. Here, we report that miR-502 targets two components in pancreatic cell lines, Ku70 and XLF of the C-NHEJ. Interestingly, we also observed an attenuated cell cycle res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This latter suggests a role for miR-622 in regulating the balance between HR and NHEJ in the cell cycle [ 30 ]. It was demonstrated that miR-502 directly targets Ku70 and XLF in pancreatic cell lines, which might modulate both the assembly of the Ku70/80 complex and final steps of ligation during NHEJ; overexpression of this miRNA makes cells susceptible to DNA damage [ 31 ].…”
Section: Ku70/80mentioning
confidence: 99%
“…This latter suggests a role for miR-622 in regulating the balance between HR and NHEJ in the cell cycle [ 30 ]. It was demonstrated that miR-502 directly targets Ku70 and XLF in pancreatic cell lines, which might modulate both the assembly of the Ku70/80 complex and final steps of ligation during NHEJ; overexpression of this miRNA makes cells susceptible to DNA damage [ 31 ].…”
Section: Ku70/80mentioning
confidence: 99%
“…A recent paper showed that miR-502 overexpression increased the radiosensitivity of pancreatic cancer cell lines by targeting two proteins of the classical NHEJ repair pathway, Ku70 and XLF [ 122 ]. Mechanistically, miR-502 directly inhibits the DNA double-strand repair and also attenuates the cell cycle response upon radiation.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, there are many examples of RNAs controlling the expression of factors involved in the NHEJ mechanism, for instance, miR-101 and miR-874-3p target DNA-PKcs (as mentioned above). miR-124, miR-502 and miR-545 regulate Ku70 [144][145][146], miR-526b, miR-622 and miR-218-5p control the level of Ku80 [89,147,148], miR-34a suppresses the expression of 53BP1 [149]. For some factors, in addition to miRNA, competing endogenous RNAs (ceRNA) have been described that are able to counteract the effects of specific miRNAs by direct binding (Figure 5) [150]; for example, miR-4727-5p was shown to inhibit the expression of DNA ligase IV, while aforementioned ceRNA lnc-RI, reversed this effect [151].…”
Section: Different Types Of Rnas Are Involved In All Stages Of Nonhommentioning
confidence: 99%